Symbiosis of centrosema pubescens with line homologous rhizobium strains - Franco, Avílio A.; Serpa, Aryno; Souto, Sebastião Manhães (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse experiment was carried out with Centrosema pubescens Benth. comparing the variety "Deodoro" with 4 of its lines, to study differences in nodulation and plant yield, utilizing several different strains of Rhizobium. For the two harvests at 28 and 56 days alter sowing, highly significant strain effects were observed in nodulation and plant growth. Differences between lines were significant only in the first harvest. Line homologous strains seemed to produce more nodules than non-homologous ones. A highly significant regression of nodule weight and total plant nitrogen was found which was independent of the Rhizobium strain or host. There was an interaction between strains and harvests and therefore it was suggested that strain precocity is not the most important characteristic to be observed in strain selection for perennial plants. The use of more than one strain in the inoculant, one precocious and another with later high efficiency should be considered.